Management of acute psychiatric emergencies: Approaches and challenges in emergency departments - Alanazi, Sultan Mohammed; Alotaibi, Hatim Faihan; Alanazi, Ibrahim Mohammed; Aldukhain, Adel Mohammad; Albasri, Rakan Faisal; Alharbi, Salman Abdullah; Alanizi, Hamoud Ghayyadh; Alharbi, Yussef Falah; Almutairi, Diyanah Bander; Alturki, Najla Abdulaziz; Alhasson, Aseel Hasson; Ghassap, Sawsan Ahmed; et al. (International journal of health sciences, 2021)
Background: The prevalence of psychiatric emergencies increases significantly during public disasters, highlighting the need for effective management strategies. Disasters, including pandemics and epidemics, exacerbate mental health conditions and strain healthcare systems. Despite established models for psychiatric emergency management, there remains a crucial need to ensure accessibility and effectiveness in such high-stress scenarios. Aims: This article aims to review and propose strategies for managing psychiatric emergencies in the context of public disasters. It focuses on evaluating the impact of crises on mental health and the capacity of healthcare systems to address these needs effectively. Methods: A comprehensive review of literature was conducted, examining psychiatric emergencies in disaster settings, including pandemics and natural disasters. The review involved analyzing current management models, assessing their effectiveness, and identifying gaps in healthcare provision. Results: The study finds that the prevalence of mental disorders during disasters is significantly higher compared to normal conditions. Key challenges include inadequate infrastructure, limited staff, and the need for specialized psychiatric interventions. Effective strategies include enhanced triage systems, increased availability of outpatient and inpatient care, and the use of telepsychiatry where applicable.